Kewarganegaraan Ganda di Indonesia : Peluang atau Ancaman bagi Partisipasi Politik - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Azzahra Azzahra; Vina Aulia Nur Pratama; Ervina Eka Saputri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study investigates the impact of dual citizenship on political participation and national identity in Indonesia. Despite dual citizenship not being officially recognized under Law No. 12 of 2006 on the Citizenship of the Republic of Indonesia, many Indonesians living abroad encounter this status. This research employs a mixed-methods approach, combining qualitative and quantitative methods, to explore the challenges faced by dual citizens in political engagement and how this status affects their political identity. Findings indicate that individuals with dual citizenship often face legal uncertainties, difficulties in political participation, and conflicts regarding political loyalty. Comparative analysis with countries that recognize dual citizenship, such as the United States and several European Union nations, reveals that acknowledging dual citizenship can facilitate better political participation and reduce identity conflicts. Based on these findings, it is recommended that Indonesia consider reforming its citizenship policies, enhance education on political rights, and strengthen international dialogue to address the challenges associated with dual citizenship.